Model Word Square : Konsep Simantik Siswa Mengenal Mufrodat pada Pembelajaran Bahasa Arab - Mualim Wijaya; Fathor Rozi; Evi Nurus Suroiyah; Wahyudi Wahyudi (PALAPA, 2023)
This study aims to see the concept of the word square model presented by the teacher to students as an effort to get to know mufrodat in learning Arabic. This study uses a qualitative approach to the type of case study. This research is located at MI Ar-Rofi'iyah, Semampir Village, Kraksaan District, Probolinggo, East Java. The source of the data was obtained through observation and interviews with 3 informants, namely the head of the Madrasah, the fifth grade teacher and the Arabic teacher. The data analysis used is owned by Milles and Hubberman namely data reduction, data display and data verification. The results of the study stated that MI Ar-Rofi'iyah applying the word square model was able to introduce students to various mufrodats and their meanings properly and correctly. The Arabic language learning model with word square is modified with 4 learning activities, namely istima', takrar, bahtsul kalimah, and tashih. Not only that, this learning model makes it easier for students to practice concentration, be observant and careful in choosing and finding answers. It can be said that this research is a new way of modifying the learning model so that it is not stuck in a boring learning concept for students by adjusting to the characteristics of students and learning needs will make it easier for teachers and students to quickly achieve learning goals.